Excluding Forced Heirs due to a Lack of Personal Relationship with the Deceased in Spain in a Comparative Perspective - Garcia-Teruel, Rosa M. (Review of European and Comparative Law, 2021)
Forced heirship is considered a limit on the freedom of will of the deceased in favour of intergenerational solidarity. It involves that some relatives, usually descendants, have the right to claim a share of the deceased’s assets or estate. Although recognized in most EU jurisdictions, authors discuss about the need to regulate this institution taking into account new family models and societal changes. In fact, this debate has been intensified due to the COVID-19 pandemic, which showed that several elders died alone in nursing homes without family support, and part of their assets shall be reserved to their relatives. This paper analyses the legal framework of forced heirship in Spain and examines to which extent it is possible to exclude this right due to a lack of personal relationship with the beneficiaries in view of comparative models.